2021
DOI: 10.3390/nu13020430
|View full text |Cite
|
Sign up to set email alerts
|

The Marine Microalga, Tisochrysis lutea, Protects against Metabolic Disorders Associated with Metabolic Syndrome and Obesity

Abstract: Long-chain polyunsaturated fatty acids n-3 series and especially docosahexaenoic acid are known to exert preventive effects on metabolic disturbances associated with obesity and decrease cardiovascular disease risk. n-3 LC-PUFAs are mainly consumed in the form of fish oil, while other sources, such as certain microalgae, may contain a high content of these fatty acids. The aim of this study was to evaluate the effects of Tisochrysis lutea (Tiso), a microalga rich in DHA, on metabolic disorders associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 92 publications
(112 reference statements)
2
16
0
Order By: Relevance
“…From a pharmacological point of view, the smaller is the concentration at which the molecule is active, the greater is its potential application. Recently, in a model of metabolic syndrome, a high-fat diet, supplemented with 12% (w/w) of freeze-dried T. lutea, significantly reduced plasma TNF-α levels and increased IL-10 in abdominal adipose tissue [43].…”
Section: Discussionmentioning
confidence: 99%
“…From a pharmacological point of view, the smaller is the concentration at which the molecule is active, the greater is its potential application. Recently, in a model of metabolic syndrome, a high-fat diet, supplemented with 12% (w/w) of freeze-dried T. lutea, significantly reduced plasma TNF-α levels and increased IL-10 in abdominal adipose tissue [43].…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen young male Wistar rats, aged three weeks, weighing about 130 g and obtained from Janvier Labs (Le Genest-Saint-Isle, France), were selected to avoid age effects on metabolic disorders associated with obesity, and to avoid any sexual endocrine fluctuation. The nutritional protocol was previously described [32,83] and all the experiments were approved by the Ethical Committee 06 Pays de la Loire and by the French Ministry of Higher Education, Research and Innovation (APAFIS 10187, 31 August 2017).…”
Section: Animal and Dietsmentioning
confidence: 99%
“…The animals were randomly divided into three groups of six rats and received diets ad libitum for eight weeks as follows: (1) the CTRL group; (2) the HF group was fed the 260 HF diet (Safe, Augy, France) with 10% fructose in ad libitum drinking tap water (Distriborg, St.-Genis-Laval, France); (3) the HF-Dia group received an HF diet supplemented with 12% (w/w) of the freeze-dried microalga D. lutheri (IBE-CNR, Florence, Italy). The amount of D. lutheri added to the diet was chosen from our previous animal studies that showed the anti-obesogenic effects of O. aurita, P. tricornutum and T. lutea marine microalgae at 12% (w/w) after eight weeks of the diet in Wistar rats [32,53,83]. These microalgae, which are rich in n-3 LC-PUFAs, showed preventive effects on obesity and metabolic disturbances associated in HF-fed Wistar rats [32,53,83].…”
Section: Animal and Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mayer et al [17] have recently studied the preventive effects of Tisochrysis lutea (Tiso) on metabolic alterations associated with obesity, including NAFLD. Wistar rats were distributed into three experimental groups and were fed with a standard diet (CTRL), a high-fat high-fructose diet (HF) with 10% fructose in drinking water, or the HF diet but supplemented with 12% of Tisochrysis lutea (HF-Tiso), for eight weeks.…”
Section: Microalgaementioning
confidence: 99%